The Therapeutic Massage for Elderly Women with Colorectal Cancer: Effects on Pain, Fatigue, And Anxiety - Ragab Arafat, Walaa Hassan; Bader El-Dien, Soheir Ali; El-Sayed Ebied, Ebtesam Mo’awad; Sobeih, Mohamed Emam (Journal of Neonatal Surgery, 2025)
Therapeutic massage (TM) can be used to relieve colorectal cancer pain, fatigue and anxiety in elderly patients. It can promote relaxation and relieve tension by applying physical pressure to muscles, tendons, and connective tissues at specific sites. This study aims to evaluate the effect of therapeutic massage on pain intensity, fatigue and anxiety level among elderly women with colorectal cancer. Design: Quasi-experimental design used to test whether a treatment or intervention affects patient outcomes. Sample: A purposive sample of 60 elderly colorectal cancer patients; 30 study and 30 control groups. Setting: the study was conducted at National Cancer Institute (inpatients and outpatient). Study tools: (1) Structured Personal and Medical Data Questionnaire, (2) Subjective & Objective colorectal cancer Pain intensity Assessment including: part1: Subjective pain intensity assessment, part2: Objective pain intensity assessment (Visual Analogue Scale (VAS): Numeric Rating Scale (NRS) and Faces Pain Rating Scale (FRS), (3) Hirai Cancer Fatigue Scale (HCFS), (4) Geriatric Anxiety Scale (GAS). Results: 40% of elderly women patients aged 65 to less than 70 years old in the study group with a mean age 67.6±5.5 years and 36.7% of women patients aged 60 to less than 65 years old in the control group with a mean age 67.5±5.6 years. 96.7%, had severe pain and 73.4% had moderate to severe anxiety during pretest which was decreased to be 96.7% had intermittent pain & 80% had mild to moderate anxiety in the study group after implementation of Therapeutic massage as compared to 46.7% of elderly patients who suffered from severe pain and 100% who suffered from moderate to severe anxiety posttest in the control group whereas Elderly women patients suffered from fatigue pre and post massage in the study and control groups. Conclusion: Therapeutic massage has a positive effect on (pain & anxiety) among colorectal cancer patients. Recommendation: application of TM on a large-scale sample to gain more generalization & endorsement of it as a routine nursing care in medical oncology units